Laboratory Methods for Rearing Horn Flies (Diptera: Muscidae). Issue 6 (2nd November 2020) - Holderman, Chris J; Sanchez-Sandoval, Ulises A; Ramirez, Jovannah; Smythe, Brandon G
Abstract: The horn fly, Haematobia irritans (L.), is an obligate hematophagous ectoparasite of cattle, and one of the most important pests of cattle causing unrealized gains or losses in meat and milk production. The present study describes the difficulties that arise when research programs have attempted to maintain this pest, both on-host and off-host, in a laboratory environment. Suggestions aimed at assisting future researchers in successfully colonizing horn flies in the laboratory are provided.